Definition of Acute Toxicity and Cumulative Properties of the Drug “Lipointersil” - Yu. Yu. Lavryshyn; B. V. Gutyj; B. M. Verveha; O. T. Kutsan; V. M. Hunchak; I. I. Khariv; V. I. Kushnir; R. O. Vasiv; Kh. Ya. Leskiv; Z. A. Guta (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The research aimed to determine the acute toxicity and cumulative properties of the liposomal drug “Lipointersil” based on interferon and spotted milk thistle. The acute toxicity of the “Lipointersil” drug was assessed in white rats, aged 2–3 months, with a body weight of 170–180 g through intragastric and intramuscular administration. After administration of the drug, the dose and the number of animals that died were recorded, and the median lethal dose (DL50) of the investigated drug was calculated using the method of H. Kerber. The cumulative properties were determined in white rats aged 2–3 months, weighing 170–185 g, using the subchronic toxicity test method by K. S. Lim et al., modified by K. K. Sydorov. Based on the conducted research, it was established that the “Lipointersil”drug, according to the State Standard of Ukraine 85.2-37-736:2011, belongs to class IV toxicity (slightly toxic substances). The LD50 for intragastric and intramuscular administration in white rats is 5166.66 and 5833.33 mg/kg of body weight, respectively. In determining of the cumulative properties of the “ Lipointersil ” drug, no deaths of experimental animals were observed during the study. Moreover, the animals remained active, fed well, and had dense, shiny fur. The coefficient of accumulation of the “Lipointersil” drug was more than 8.31 units, indicating its weakly pronounced cumulative properties. Prolonged daily administration for 24 days of “Lipointersil” had no significant impact on the functional state of the liver and kidneys. Under long-term (24 days) daily administration in increasing doses, the drug “Lipointersil” caused slight destruction of hepatocyte membranes, as indicated by the increased activity of alanine and aspartate aminotransferases and alkaline phosphatase.